2020
DOI: 10.1021/acsami.0c05379
|View full text |Cite
|
Sign up to set email alerts
|

Plasticizer-Free Thin-Film Sodium-Selective Optodes Inkjet-Printed on Transparent Plastic for Sweat Analysis

Abstract: A novel strategy to functionalize transparent flexible plastic films with an optical ion-sensing layer using an inkjet-printing technology is described. The hydrophobic sensing chemicals that include a sodium ionophore, a lipophilic proton chromoionophore, and a lipophilic ion-exchanger are co-deposited onto substrates such as transparent polyester film sheets in the absence of any plasticizer and/or hydrophobic polymer matrix. The inkjet-printing process enables the formation of optode films with nanoscale th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Section 2.1.2) have been used in many wearable devices. [133][134][135][136][137][138] Color changes can be detected by the Figure 6. Electrochemical sensors for wearable applications.…”
Section: Colorimetric Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Section 2.1.2) have been used in many wearable devices. [133][134][135][136][137][138] Color changes can be detected by the Figure 6. Electrochemical sensors for wearable applications.…”
Section: Colorimetric Sensorsmentioning
confidence: 99%
“…[139] Colorimetric sensors can be fabricated on different wearable substrates, such as paper, [140] hydrogel, [141] fiber, [142] fabric, [143] and yarn. [133,134] Wearable colorimetric devices include onskin platform, [135,144,145] smart band, [143] wristband, [146] contact lenses, [138] T-shirt, [133] etc., and are usually used to detect human sweat, [136,137,143] tears, [138] VOCs, [134] UV, [147] etc. Kim et al [134] demonstrated an eye-readable and wearable H 2 S sensing platform based on colorimetric dye-loaded nanofiber yarn, which could be incorporated into a worker's garment as a visual indicator; and was adequate for inexpensive mass-production (Figure 7A).…”
Section: (9 Of 20)mentioning
confidence: 99%
“…An ISM as understood here is a system as typically used in potentiometric sensors: a membrane containing ionophore—a ligand able to preferentially bind analyte ions (called primary ions) in the lipophilic medium [ 1 , 2 ]. Due to the presence of a highly selective ionophore, the ISM allows determination of contents of free ions of interest, in the presence of other chemical forms of analyte, in complex matrices, including blood, serum or environmental samples [ 3 , 4 , 5 , 6 , 7 , 8 ]. This makes ISM-based sensors attractive tools for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…We recently discovered that these hydrophobic sensing chemicals readily adsorb on hydrophilic substrates such as cellulose paper, enabling ion sensing in the absence of a plasticized polymer matrix. [12][13][14][15] The optode cocktail without the plasticized polymer becomes inkjet-printable because of its ideal viscosity and surface tension. As a result, ISOs can be fabricated in an unprecedentedly precise and reproducible fashion, making batch calibration possible.…”
mentioning
confidence: 99%
“…This optode is also reversible and has a 90% response time of <2.5 min. When a commonly used ionophore, sodium ionophore VI, 12,15 is printed along with Chromoionophore I and KTFPB to create Na + optodes, the reversibility is unsatisfactory (Fig. 4A).…”
mentioning
confidence: 99%